Chapter Institutional Learning in Higher Education and Graduate Transitions - Federighi, Paolo (Studies on Adult Learning and Education, 2023)
The 'learning exclusion equilibrium' strategy in Italy also governs young adults' possibilities of accessing higher education institutions (HEIs) and entering and being successful on the labour market. The upshot of this strategy has been to weaken the social role of universities and open the field to new players promoting new solutions based on stronger teaching and research partnerships. After graduation, young university leavers face a period in which they follow non-linear paths as they try to fit their skills to the labour market demand. For many professions, there has been an immense change in this demand. Now, unlike the past, life skills are considered basic competences for technical professions too. If those lacking these skills enter the labour market later, the problem arises of how to create these competences both during the period of university education and in the following years. Universities have to practise institutional learning and study with those who need knowledge in order to come up with a new strategy so that their graduates can directly manages their relations with the labour market. Knowledge of the situation and development of graduates' professional lives is needed in order to give academic programmes a new direction and allow students to make an informed choice of which university to enrol in. The European Graduate Tracking Initiative can lead the way towards this goal.